MANAGEMENT OF INTRACANAL SEPARATED INSTRUMENTS: FACTORS CONTRIBUTING TO ENDODONTIC FILE SEPARATION — A NARRATIVE REVIEW - Tareq Hajaj; Paul Freiman; Serban Talpos Niculescu; Mihai Rominu; Tiberiu Hosszu; Ioana Veja (Romanian Journal of Oral Rehabilitation)
"Background: Instrument separation during endodontic therapy remains a significant clinical challenge, often impacting treatment outcomes. Despite advances in metallurgy and instrument design, file fracture continues to be unpredictable. Objective: This review explores the contributing factors to file separation, evaluates current management strategies, and outlines preventive measures to enhance clinical success. Methods: A narrative review of literature from PubMed, Scopus, and Google Scholar using keywords including ""endodontic file separation,"" ""fractured instruments,"" and ""retrieval techniques"". Articles published between 2000 and 2025 (41 articles reviewed) were included. Studies were selected based on relevance, recency, and clinical applicability. Inclusion criteria included clinical studies, reviews, and case series addressing separated instrument management; exclusion criteria involved non-English studies and in vitro-only reports. Results: Contributing factors include torsional and cyclic stress, inadequate access, overuse of files, and canal complexity. Management strategies include conservative retention, bypassing, and complete retrieval, often under magnification and ultrasonic assistance. Preventive measures are critical in mitigating risk. Conclusion: A comprehensive understanding of fracture mechanisms and management options can guide clinicians in optimizing endodontic outcomes while preserving tooth integrity. Future perspectives include the use of guided endodontics and AI-assisted detection of high-risk canals."